F, Cl and S input via serpentinite in subduction zones: implications for the nature of the fluid released at depth. (17th October 2013) - Debret, Baptiste; Koga, Kenneth T.; Nicollet, Christian; Andreani, Muriel; Schwartz, Stéphane
Abstract The abundances of F, Cl and S in arc magmas are systematically higher than in other mantle‐derived magmas, suggesting that these elements are added from the slab along with H2O. We present ion probe microanalyses of F, Cl and S in serpentine minerals that represent the P–T evolution of the oceanic lithosphere, from its serpentinization at the ridge, to its dehydration at around 100 km depth during subduction. F, Cl and S are incorporated early into serpentine during its formation at mid‐ocean ridges, and serpentinized lithosphere then carries these elements to subduction zones. More than 50% of the F, Cl and S are removed from serpentine during the prograde metamorphic lizardite/antigorite transition. Due to the low solubility of F in water, and to the low amount of water released during this phase transition, the fluids mobilizing these elements must be dominated by SOX rather than H2O.